Inventarisasi Parasitoid Larva Hama Penggulung Daun Pisang (E. Thrax L.) Di Desa Sampali Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Ameilia Zuliyanti Siregar; M Hafizhan Lubis; Mukhtar Iskandar Pinem (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
Deli Serdang is the district with the highest banana production in North Sumatra. The main pest is Erionota thrax. And one of the natural enemies used for control is parasitoids. The purpose of this study was to determine the parasitoid larvae of the banana leaf rolling pest (Erionota thrax) and to calculate the level of pest attack in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency and insect identification activities were carried out at the Pest and Plant Disease Laboratory, Faculty of Agriculture, University North Sumatra. The research method used a random sampling method, carried out in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency. ByOtherwise, calculating pest population density and pest attack rate done. The results showed two types of parasitoids, namely Cotesia erionotae and Brachymeria lasus were idinfied. The highest population density of E. thrax in Barangan banana was 1.63, the highest population density of E. thrax in Kepok banana was 1.45. The attack rate of E. thrax on Barangan bananas reached 95%, and the attack rate of E. thrax on Kepok bananas reached 97.5%. Keywords: inventory, Erionota thrax, parasitoid, Barangan banana, Kepok banana